Carbene-catalyzed asymmetric modification of carboxylic acids and sulfonamides - Liu, Yingguo (Nanyang Technological University, 2020)
In this thesis, we demonstrated the new reaction mode enabled by NHC in the enantioselective synthesis of 3-substituted phthalides, which could be used for structural modification on heteroatoms within the medicinally significant molecules. Our method shall expand the synthetic toolbox and bring significant values for the discovery and manufacturing of better chiral prodrugs in enantiomerically enriched forms. In this thesis chapter 1 delivers the brief introduction on the chemical modification, molecular modification as prodrugs, and phthalidyl prodrugs. We also introduced briefly reaction modes enabled by NHCs and key intermediates within them. Chapter 2 demonstrates that synthetic challenges in enantioselective modification of carboxylic acids into enantiopure phthalidyl esters were addressed. Such reaction involves a chiral carbene-catalyzed asymmetric addition of a carboxylic acid to a catalyst-bound intermediate generated from a phthalaldehyde substrate. A broad range of carboxylic acids worked effectively under mild and transition metal-free conditions. Selected modified drugs demonstrated improved bioactivities against tumor cell growth. Chapter 3 describes that the methodology was extended to the compounds with modifiable nitrogen atoms. With benzenesulfonamides as substrates, the 3-(N-substituted) aminophthalides were synthesized in excellent yield and excellent enantiomeric ratios (up to 99% and 99:1). This is the first enantioselective synthesis of chiral aminophthalides. More application is under investigation.